2017
DOI: 10.3389/fpsyg.2016.02068
|View full text |Cite
|
Sign up to set email alerts
|

Expected Hierarchical Integration Reduces Perceptions of a Low Status Group as Less Competent than a High Status Group While Maintaining the Same Level of Perception of Warmth

Abstract: The compensation effect, namely people’s tendency to judge one group more positively on some dimensions and the other group more positively on other dimensions, has been validated using real social categories and experimentally created groups. However, less attention has been paid to whether and how changes in social structure affect the emergence of the compensation effect. The present research first replicated the compensation effect using Chinese participants (Study 1). Then, two studies were conducted to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The current research reveals that authoritative criticism can lower ingroup favoritism. Similarly, a recent study (Dang, Liu, Liang, & Ren, 2016) also showed that group members no longer manifested ingroup favoritism when their superior status was criticized as being illegitimate by an authoritative source. It thus can be seen that to suppress individuals' ingroup favoritism and promote social fairness, the role of authoritative third parties is crucial.…”
Section: Discussionmentioning
confidence: 91%
“…The current research reveals that authoritative criticism can lower ingroup favoritism. Similarly, a recent study (Dang, Liu, Liang, & Ren, 2016) also showed that group members no longer manifested ingroup favoritism when their superior status was criticized as being illegitimate by an authoritative source. It thus can be seen that to suppress individuals' ingroup favoritism and promote social fairness, the role of authoritative third parties is crucial.…”
Section: Discussionmentioning
confidence: 91%